Analysis of Anti-Bacterial Activity of Ethanol Extract Fragrant Pandan Leaves (Pandanus amaryllifolius Roxb) Against the Growth of Disease Cause Pathogen Bacteria Using the Agar Diffusion Method - Cut Eliza Hidayani; Chrismis Novalinda Ginting; Linda Chiuman (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Fragrant pandan (Pandanus amaryllifolius Roxb.) is a plant commonly used as fragrance and food coloring. Fragrant pandan contains many substances or bioactive compounds that have medicinal properties so they are also used as traditional medicine. One of the properties of fragrant pandan is as an antimicrobial (antibacterial and antifungal) which is thought to come from the content of alkaloids, flavonoids, phenolics, as well as steroids and terpenoids. This study aims to determine the inhibitory power of fragrant pandan extract (EPW) against the growth of pathogenic bacteria. The test method used is the agar diffusion method by looking at the temperature comparison. Time and Ph.